METHODICAL ASPECTS OF CONTROL OF THE EXPENDITURE OF THE INTERBUDGETARY TRANSFERS - Anna Anatolyevna Babich (Вестник Северо-Кавказского федерального университета, 2022)
In article is presented methodical ensuring control process of an expenditure of the budgetary resources, on the example of means of the subventions, territorial subjects of the Russian Federation allocated to executive authorities.